A VOCALIZAÇÃO DO ESCRITO E AS ALTERAÇÕES GRÁFICO-ACENTUAIS NO PORTUGUÊS OFICIAL (Polifonia, 1995)
ABSTRACT: This study, based on a research carried on São Paulo, between 1989 and 1990, shows that speakers from differnt age, sex and school background have their linguistuic performance (vocalization) affected by spelling reforms, especially, the changes made in the graphic stress norms.